PENATAAN DAN PENGEMBANGAN DESA WISATA KEMBANG KUNING, LOMBOK TIMUR - Sari, Dewi Lintang; Juliansyah, Irgi Zaini; Suryadini, Aisha Suci; Haerunisa, Haerunisa; Tiana, Elia Marta; Isnaeni, Isnaeni; Sholihattri, Wina; Abdillah, Roby; Hadi, M. Warisul; Azka, Aril Danish (Universitas Mataram, 2024)
Indonesia has great potential for natural and cultural tourism, contributing significantly to the country's foreign exchange, with revenues of US14 billion in 2023. Lombok, as a major destination, recorded an increase in foreign tourists by 56.27% in February 2024. Kembang Kuning Village in East Lombok, which was inaugurated as a tourist village in 2019, continues to develop with various achievements and is the focus of tourism development through the Mataram University KKN-PMD program. The purpose of the Mataram University KKN-PMD is to explore the potential of the Kembang Kuning Tourism Village, provide a forum for implementing the Tri Dharma of Higher Education, especially in the Dharma of Community Service, and expand opportunities for tourism development. The implementation of the Mataram University KKN-PMD in Kembang Kuning Village involves providing materials, field surveys, and compiling a work program for 45 days. The main program focuses on digital marketing strategies to increase tourist visits. This village offers stunning natural panoramas, unique waterfalls, and interesting cultural attractions. Local homestays provide educational experiences such as making coconut oil and coffee. KKN-PMD students of Mataram University contribute to village development through various initiatives, including village planning, digital tourism socialization, and village promotion through social media. Activities such as village cleaning, establishing reading corners, and 17 August events are also carried out to increase tourist attractions and community welfare. Kembang Kuning Village, East Lombok, offers natural beauty, authentic culture, and education, making it an ideal destination for tourists. Collaborative efforts from various parties are needed to ensure the sustainability and preservation of the village's culture and environment.